We are Appalachian Christians: Wait, can we say that? - Melissa Comer; Kathy Brashears (University of Johannesburg, 2020)
Considering the question: 'can we say that we're Southern Appalachian Christians in the world of academia?', the authors examine the answer amid diverse people groups while reflecting on their personal cultures as Appalachian women, Appalachian storytellers, and, yes, Appalachian Christians. Acknowledging that cultural influences impact their lives in academia, they explore how faith is often perceived in higher education. Living in the Southern United States, in the heart of Appalachia, in an area readily identified as the Bible-Belt, the authors use storytelling as a vehicle for examining intolerance as well as for thinking about what it means to be tolerant. Framed within a diversity and equity model of thinking, they provide a thought-provoking probe: have we entered a world where religious intolerance, specifically that of Christian beliefs, is acceptable? Keywords: Tolerance, Equity, Academia, Storytelling, Culture, Christians, Appalachia How to cite this article: Comer, M. & Brashears, K. 2020. We are Appalachian Christians: Wait, can we say that?. Scholarship of Teaching and Learning in the South. 4(2): 218-227. https://doi.org/10.36615/sotls.v4i2.126. This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/